Research-based exhibition development: Illustrating the invisible nanoworld - Laherto, Antti (LUMAT: International Journal on Math, Science and Technology Education, 2018)
Informal learning environments such as exhibitions in museums and science centres have the potential to promote public engagement in the societally important fields of nanoscience and nanotechnology (NST). This study contributes to research-based development of an NST exhibition by mapping educational, communicational and museographical challenges in illustrating nanoscale science. For the methodological framework, the study employs a previously suggested model based on the Model of Educational Reconstruction. Potential visitors’ perspectives were analysed by reviewing research literature on NST learning, and by interviewing science centre visitors. On the basis of the results, the study suggests strategies for illustrating the nanoscale in an exhibition: ways of supporting visitors’ scale conceptualisation, presenting images and visualisations deliberately, and using scale models and macroscopic analogies. The study examines how the educational role of science centres may be enhanced by informing exhibition development with visitor-oriented research.